Evaluation of the UNED MOOCs Implementation: Demographics, Learners' Opinions and Completion Rates - Gil-Jaurena, Inés; Callejo-Gallego, Javier; Agudo, Yolanda (International Review of Research in Open and Distributed Learning, 2017)
The paper is a study about the MOOC experience at the Spanish National University of Distance Education (UNED), where we have collected initial and final information about learners' profiles and opinions, as well as enrolment, completion and certification rates. It is a survey-based study covering 17 MOOCs offered in UNED's own platform, and collects information from a sample of more than 24000 learners (initial survey) and 2003 learners (final survey). The paper first presents an overview of the MOOC experience at UNED, introducing the main features of these courses. Afterwards, it focuses on the methodology used in the study and in the information gathered in the second edition of UNED MOOCs, which took place from November 2013 until March 2014. Learners' average profile is a Spanish female, approximately 37 years old, with a University degree, and generally employed. For many of the participants, UNED MOOCs were their first experiences with these sorts of courses, and the main reasons for enrolment were the course topic and the perceived usefulness for professional development. The expectations regarding completion and certification where initially very high, but completion rates remain below 14%. In the final survey, the overall experience in the MOOCs and the different tools used in the courses were highly valued by learners, except the support figures (curator, facilitator, peers), which received lower ratings. These findings are of interest for the institution and further research, refining learning analytics, is encouraged.